2015
DOI: 10.1002/2014jf003252
|View full text |Cite
|
Sign up to set email alerts
|

The life of a meander bend: Connecting shape and dynamics via analysis of a numerical model

Abstract: Analysis of bend‐scale meandering river dynamics is a problem of theoretical and practical interest. This work introduces a method for extracting and analyzing the history of individual meander bends from inception until cutoff (called “atoms”) by tracking backward through time the set of two cutoff nodes in numerical meander migration models. Application of this method to a simplified yet physically based model provides access to previously unavailable bend‐scale meander dynamics over long times and at high t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
56
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 82 publications
(57 citation statements)
references
References 99 publications
(133 reference statements)
1
56
0
Order By: Relevance
“…In order to account for the effects of variable migration rates, we normalized all storage durations by the time required for the channel to migrate laterally to the point of meander bend cutoff (T cut ). In our model simulations, we explicitly tracked meander bends from growth to cutoff following the approach of Schwenk et al (2015). While the cutoff time varied in the model runs, the peak of the probability distribution function occurred for T cut = 350 years.…”
Section: Scaling Model Results To Natural Systemsmentioning
confidence: 99%
“…In order to account for the effects of variable migration rates, we normalized all storage durations by the time required for the channel to migrate laterally to the point of meander bend cutoff (T cut ). In our model simulations, we explicitly tracked meander bends from growth to cutoff following the approach of Schwenk et al (2015). While the cutoff time varied in the model runs, the peak of the probability distribution function occurred for T cut = 350 years.…”
Section: Scaling Model Results To Natural Systemsmentioning
confidence: 99%
“…Equation is less sensitive to noise in the input coordinates when the derivatives are approximated with centered differences [cf. Schwenk et al , ]. The calculation of curvature is notably affected by noise and often requires some level of smoothing.…”
Section: Methodsmentioning
confidence: 99%
“…In their review, Blum et al (2013) concluded that lateral migration is the primary process widening incised channels into valleys in response to base-level fall. This conclusion corresponds to positive relationships between channel-bed slope and lateral bend migration, which is widely implemented in numerical simulations of channel meandering (Howard and Knutson, 1984;Gran et al, 2013;Schwenk et al, 2015). Most of the models are restricted to simulations of neck cutoffs, as a result of the difficulty of predicting and simulating chute cutoffs (Seminara, 2006).…”
Section: Introductionmentioning
confidence: 90%